Investigating the Influence of (Deoxy)fluorination on the Lipophilicity of Non‐UV‐Active Fluorinated Alkanols and Carbohydrates by a New log P Determination Method. (23rd November 2015) - Linclau, Bruno; Wang, Zhong; Compain, Guillaume; Paumelle, Vincent; Fontenelle, Clement Q.; Wells, Neil; Weymouth‐Wilson, Alex
Abstract: Property tuning by fluorination is very effective for a number of purposes, and currently increasingly investigated for aliphatic compounds. An important application is lipophilicity (log  P ) modulation. However, the determination of log  P is cumbersome for non‐UV‐active compounds. A new variation of the shake‐flask log  P determination method is presented, enabling the measurement of log  P for fluorinated compounds with or without UV activity regardless of whether they are hydrophilic or lipophilic. No calibration curves or measurements of compound masses/aliquot volumes are required. With this method, the influence of fluorination on the lipophilicity of fluorinated aliphatic alcohols was determined, and the log  P values of fluorinated carbohydrates were measured. Interesting trends and changes, for example, for the dependence on relative stereochemistry, are reported.